Digital Learning Tools and Critical Thinking: A Study on Nearpod-Integrated Worksheets in Elementary School - Harmoni, Caesarea Zahra; Handayani, Sri Lestari (FKIP - Universitas Riau, 2025)
Critical thinking skills are essential for students to face 21st-century challenges. This study aims to analyze the impact of implementing Interactive Digital Worksheets (IDWs) through the Nearpod platform on improving critical thinking abilities among fifth-grade students at SD Islam Ruhama. A quantitative approach using a quasi-experimental design—specifically the Nonequivalent Control Group Design—was employed. The sample consisted of 39 students divided into experimental and control groups. Data were collected using essay-type questions based on Ennis’ FRISCO framework, which had been validated and tested for reliability. An Independent Sample T-Test revealed a significant difference in post-test scores between the two groups, with a p-value less than 0.05. The effect size was calculated at 0.94572, indicating a high magnitude of influence. These results suggest that IDWs have a substantial positive impact on students’ critical thinking development. Therefore, integrating IDWs via Nearpod can serve as an effective instructional strategy aligned with 21st-century learning competencies.